Legacy of Hans Rosling - Ottersen, Ole Petter (Socialmedicinsk tidskrift, 2018)
The subtitle of Hans Rosling’s memoirs reads as follows: How I got to understand the world (Hur jag lärde mig förstå världen). The subtitle could just as well have read: How I taught the world to understand itself. For this is the legacy of Hans Rosling: He provided us all with new and fundamental insight about the world and its development. He did so compellingly, passionately, and with an optimism that both encouraged and inspired.